N-Cadherin Prodomain Processing Regulates Synaptogenesis - Reines, Analia Gabriela (2012)
Classical cadherins, which are adhesion molecules functioning at the CNS synapse, are synthesized as adhesively inactive precursor proteins in the endoplasmic reticulum (ER). Signal sequence and prodomain cleavage in the ER and Golgi apparatus, respectively, activates their adhesive properties. Here, we provide the first evidence for sorting of nonadhesive precursor N-cadherin (ProN) to the neuronal surface, where it coexists with adhesively competent mature N-cadherin (N-cad), generating a spectrum of adhesive strengths. In cultured hippocampal neurons, a high ProN/N-cad ratio downregulates synapse formation. Neurons expressing genetically engineered uncleavable ProN make markedly fewer synapses. The synapse number can be rescued to normality by depleting surface ProN levels through prodomain cleavage by an exogenous protease. Finally, prodomain processing is developmentally regulated in the rat hippocampus. We conclude that it is the ProN/N-cad ratio and not mature N-cad alone that is critical for regulation of adhesion during synaptogenesis.